Successful operative treatment of uterine leiomyoma with extensive intravenous extension to the IVC, right heart, and pulmonary arteries. Issue 3 (4th May 2019) - Brar, Ranjeet; Skervin, Alicia; El-Sakka, Karim; Fish, Andrew; Lewis, Michael
Abstract: Introduction: Intravenous extension of benign uterine leiomyomata ('fibroids'), in the absence of discrete metastatic disease has rarely been reported. 'Fibroids' remain one of the most common premenopausal uterine pathologies. Methods and results: We report the diagnosis and multidisciplinary led operative management of a 52-year-old woman with a histologically benign, but biologically aggressive, uterine leiomyoma with intravenous extension to the inferior vena cava (IVC), right heart and pulmonary arteries. Conclusions: Total abdominal hysterectomy and bilateral salpingo-oophorectomy combined with exploration of the sub-hepatic IVC and heart under deep hypothermic circulatory arrest achieved its successful macroscopic clearance.